Physical Properties of Soils in Relation to Erosion in Morena Tebsil of M.P. - Misra, V.K.; Khanvilkar, V.G. (Journal of Soil and Water Conservation, 2022)
Large area of Morena tehsil is lying sheet eroded and infested with huge ravines and gullies. This erosion is spreading at a rapid speed and is engulfing vast area of cultivable land. The speed of erosion however differs from place to place. As the climate and vegetation of the tehsil is almost uniform throughout the area, it was thought that variation in the erodibility of the soils might be due to the physical properties of soils in addition to topography and other inherent soil properties. Some of the important physical properties which classify the soil into erosive and nonerosive categories, are those of texture, dispersion ratio, ratio of colloid to moisture equivalent and erosion ratio. Since no such data for these soils is available, the objective of the present study was to investigate the soil characteristics responsible for the erosion in these soils and to suggest measures for preventing further erosion in the soils of the tehsil